2001
DOI: 10.1007/s11746-001-0310-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of (e)‐11‐hydroxy‐9‐octadecenoic acid and (E)‐9‐hydroxy‐10‐octadecenoic acid by biotransformation of oleic acid by Pseudomonas sp. 32T3

Abstract: Pseudomonas sp. 32T3, a newly identified strain originally isolated from a vegetable oil-contaminated soil, produces three monohydroxy acids-(E)-11-hydroxy-9-octadecenoic acid, (E)-10-hydroxy-8-octadecenoic acid, and (E)-9-hydroxy-10-octadecenoic acid-as bioconversion products of oleic acid. The bacterial cells were grown in a mineral medium containing oleic acid as the main carbon substrate. The compounds were identified as the corresponding methyl esters on the basis of their chromatographic and spectroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Compounds 7 and 12 – 14 , identified as saturated keto fatty acids, were previously prepared from biotransformation or isolated from a few higher plants. From the CID spectra of [M − H + 2Na] + ions of these compounds, the β ion of 7 , 12 , 13 , and 14 was observed at m / z 187, 187, 201, and 215, respectively, whereas the γ′ ion of 7 , 12 , 13 , and 14 was found at m / z 257, 257, 271, and 285, respectively. These diagnostic ions led to the identification of the position of the keto group at C-10 for 7 and 12 , C-11 for 13 , and C-12 for 14 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds 7 and 12 – 14 , identified as saturated keto fatty acids, were previously prepared from biotransformation or isolated from a few higher plants. From the CID spectra of [M − H + 2Na] + ions of these compounds, the β ion of 7 , 12 , 13 , and 14 was observed at m / z 187, 187, 201, and 215, respectively, whereas the γ′ ion of 7 , 12 , 13 , and 14 was found at m / z 257, 257, 271, and 285, respectively. These diagnostic ions led to the identification of the position of the keto group at C-10 for 7 and 12 , C-11 for 13 , and C-12 for 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Scheme 2 outlines the synthetic path of the brominated and phenyl-substituted derivatives. The brominated analogues (29)(30)(31)(32)(33)(34)(35)(36) were formed by the bromination of the enone fatty acids (15-19, 9, 10, and 20) using Br 2 in CCl 4 followed by base-catalyzed elimination. Subsequent Suzuki coupling of some brominated compounds (29, 31, 35, and 36) with phenylboronic acid mediated by tetrakis(triphenylphosphine)palladinium(0) afforded the corresponding phenyl-substituted analogues (37)(38)(39)(40).…”
Section: Anti-inflammatory Constituents Of Gracilariamentioning
confidence: 99%
“…Plants are the main suppliers of hydroxy fatty acids, with castor oil the most common; due to the variety of possible industrial applications of ricinoleic acid, research has been done to find the best method to produce engineered castor oil (Naughton, 1974;Kinney, 2002). In microorganisms hydroxy fatty acids are produced from the biotransformation of unsaturated fatty acids (Culleré et al, 2001;Rodríguez et al, 2001;Kuo et al, 2002). Such compounds belong to a class of oxylipins with antifungal activity which have been found in Oryza sativa plants resistant to rice blast disease, and isolated from timothy plants infected by the fungus Epichloe typhina ( Kato et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…As an example, three different unsaturated monohydroxy derivatives of oleic acid (11-hydroxy-9-octadecenoic, 10-hydroxy-8-octadecenoic and 9-hydroxy-10-octadecenoic acids) are produced when Pseudomonas sp. 32T3 grows in a mineral medium with oleic acid as the main carbon substrate [4]. It has been reported that the microbial oxidation of oleic acid with Pseudomonas sp.…”
Section: Introductionmentioning
confidence: 99%